Virtual Da'wah Authority in Tafsir Rahmat H. Oemar Bakry: An Analysis of Intertextuality from Julia Kristeva - Hidayat, M. Riyan; Wijaya, Roma; el-Feyza, Muhafizah; HS, Muh. Alwi; Akmaluddin, Muhammad; Nazarmanto, Nazarmanto (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2023)
Religious activities in Indonesia suffered such massive turmoil that social media was used as a container. Then, the devotion performed by one individual is an obligation for Indonesian Muslims and the world. The spread of religious content in the virtual world seemed to upset Muslim viewers about the authenticity and validity of the source of the content distributed by an account on social media of various platforms. However, through the Book of Mercy, the author sees that there is an offer of innovation about the virtual authority of prophecy so as not to cause a faulty expansion of science. What's more, the diverse understanding of content creators has the potential to complain to the sheep and spread propaganda to the general public. Through a library-based study using the intertextuality glasses that were designed by Julia Kristeva, the message and substance of H. Oemar Bakry's offer to look at the problem will be depicted. Thus, this paper aims to respond to the new offer by creating an agency under the government's auspices of virtual authority. The aim is to counteract the provocative, tendentious, biased, subjective, and evocative messages that float in the virtual universe. Starting from this research, it will be illustrated that this study has produced a new finding that H. Oemar Bakry offers the meaning of forming a strong, honest, and orderly group of preachers. The function of the jury is to be a source of reference for the treasures of Indonesian Islamic sciences.Abstrak: Kegiatan dakwah di Indonesia mengalami gejolak yang begitu besar, dimana sosial media digunakan sebagai wadahnya. Kemudian, dakwah yang dilakukan dari satu individu merupakan kewajiban muslim Indonesia dan dunia. Penyebaran konten dakwah dalam dunia virtual seakan meresahkan para viewers muslim tentang keaslian dan keotentikan sumber konten yang disebarkan oleh sebuah akun di media sosial dari berbagai flatform. Namun, melalui Tafsir Rahmat penulis melihat bahwa ada tawaran kebaharuan tentang otoritas dakwah virtual agar tidak terjadinya ekspansi ilmu yang cacat. Terlebih lagi, pemahaman yang beragam dari para content creator berpotensi mengadu domba dan menyebarkan propaganda di khalayak luas. Melalui kajian yang berbasis kepustakaan (library research) dengan menggunakan kacamata intertekstualitas yang dipelopori oleh Julia Kristeva akan tergambar pesan dan substansi tawaran H. Oemar Bakry dalam melihat problematika tersebut. Dengan demikian, tulisan ini bertujuan merespon tawaran baru dengan membuat sebuah lembaga di bawah nauangan pemerintah tentang otoritas dakwah virtual. Tujuannya untuk menanggulangi pesan-pesan dakwah yang sifatnya provokatif, tendensius, bias, memihak, subjektif, evokatif yang berseliweran di jagad maya. Hasil dari penelitian ini akan tergambar bahwa kajian ini telah menghasilkan temuan baru bahwa H. Oemar Bakry menawarkan makna akan dibentuk kelompok juru dakwah yang kuat, jujur, dan teratur. Fungsi dari juru dakwah yakni menjadi sumber referensi khazanah keilmuan Islam Indonesia.